Bacteria cell templated porous polyaniline facilitated detoxification and recovery of hexavalent chromium. Issue 35 (23rd August 2018) - Gong, Kedong; Guo, Siyuan; Zhao, Yue; Hu, Qian; Liu, Hu; Sun, Dezhi; Li, Min; Qiu, Bin; Guo, Zhanhu
Abstract : Increased porosity and H + storage capacity by the bacteria templated-PANI facilitate improved Cr(vi ) detoxification and subsequent recovery. Abstract : In this study, bacteria cells served as a novel green pore-forming agent and template to fabricate porous polyaniline (Bac@PANI) by in situ oxidative polymerization. The achieved specific surface area of 51.2 m 2 g −1 for Bac@PANI at a bacteria dosage of OD600 = 0.536 was far higher than that of the pristine PANI (27.5 m 2 g −1 ). The Bac@PANI presented an emeraldine form, hydrophilicity and decreased isoelectric point (4.2) after being modified by bacteria. All these properties contributed to an enhanced removal performance of hexavalent chromium (Cr(vi )), with a high removal rate of 0.5 mg (min −1 ·g −1 ) and capacity of 835.06 mg g −1 of Bac@PANI. Efficient removal was achieved in both acidic and neutral solutions due to its high H + storage capacity. More than 90% of Cr(vi ) can be reduced to trivalent chromium (Cr(iii )) by oxidation of amide groups in both acidic and neutral solutions. These Cr(iii ) ions can be adsorbed by Bac@PANI simultaneously, resulting from the reversal of negative surface charge after treatment of Cr(vi ); then Bac@PANI can be easily recovered in an acidic solution.